2013
DOI: 10.1016/j.jfludis.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of stuttering: 21st century advances

Abstract: Epidemiological advances in stuttering during the current century are reviewed within the perspectives of past knowledge. The review is organized in six sections: (a) onset (b) incidence (c) prevalence (d) developmental paths, (e) genetics and (f) subtypes. It is concluded that: (1) most of the risk for stuttering onset is over by age 5, earlier than has been previously thought, with a male-to-female ratio near onset smaller than what has been thought, (2) there are indications that the lifespan incidence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
290
3
49

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(353 citation statements)
references
References 108 publications
(194 reference statements)
11
290
3
49
Order By: Relevance
“…As noted above, reliance on parental report without priming parents for which speech features to monitor for may have resulted in cases of mild stuttering being missed. Nonetheless, parental report of stuttering is usually highly accurate (Einarsdottir & Ingham, 2009;Reilly et al, 2009;Yairi & Ambrose, 2005), and the validity of the present study is further supported by the fact that the male:female ratio is consistent with that found in other studies where stuttering has been diagnosed by a clinician (Yairi & Ambrose, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…As noted above, reliance on parental report without priming parents for which speech features to monitor for may have resulted in cases of mild stuttering being missed. Nonetheless, parental report of stuttering is usually highly accurate (Einarsdottir & Ingham, 2009;Reilly et al, 2009;Yairi & Ambrose, 2005), and the validity of the present study is further supported by the fact that the male:female ratio is consistent with that found in other studies where stuttering has been diagnosed by a clinician (Yairi & Ambrose, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…1 Data on the prevalence of stuttering are limited, but one study of 12,000 Australian individuals of all ages found a prevalence of 0.72 %, which is comparable to estimates of the prevalence of blindness or rheumatoid arthritis. [2][3][4] Stuttering frequency and severity are often increased in situations of high stress, when talking on the telephone, or when talking with authority figures like police officers or physicians. 5 Discomfort about speaking can lead to prominent avoidance behaviors, such as opting out of social or workplace obligations.…”
Section: Introductionmentioning
confidence: 99%
“…A dadogĂĄs kialakulĂĄsa leggyakrabban 5 Ă©ves kor körĂŒl kezdƑdik; eurĂłpai Ă©s amerikai statisztikĂĄkra alapozva a prevalenciĂĄja 1-2%-ra tehetƑ, 3-4-szeres fiĂștöbbsĂ©ggel [5]. KĂ©t csoportja lĂ©tezik: a tĂłnusos dadogĂĄs, amely sorĂĄn az illetƑ egy-egy szĂłtagot ismĂ©tel meg többször, valamint a clonusos dadogĂĄs, amikor a gyermek a hang kimondĂĄsa Ă©rdekĂ©ben tesz görcsös erƑfeszĂ­tĂ©seket [6].…”
unclassified